Post-Yolanda assessment of damage, recovery, and regenerative capacity of natural and planted mangroves in Quinapondan, Eastern Samar - Ecaldre, Rudmar Angelo L. (Rudmar Angelo L. Ecaldre, 2014)
This study focuses on the impacts of typhoon Haiyan/Yolanda on the natural and planted mangrove ecosystems of Quinapondan, Eastern Samar. The purpose of this study was to assess the damage brought about by typhoon Haiyan on the magroves, and to determine the recovery rate and regenerative capacity of the mangrove stands at Quinapondan. The methods by Katherisan (n.d.) and English et al (19994) were used in this study and some modifications were employed to fit the situation. Trees and seedlings were counted within the plots and the trees were classified as partially damaged, severely damaged, or totally damage. A total of 239 and 229 trees were found within the nine plots for Brgy. Sto. Niño is composed of nine species namely, Acanthus ebrateatus, Aegiceras floridum, Acrostichum speciosum, Bruguiera gymnnorhiza, Nypa fruticans, Pemphis acidula, Rhizophora apiculata, Rhizophora stylosa, Xylocarpus granatum, while only two species were present at the planted mangroves stand Brgy. Sta. Margarita which were Rhizophora apiculata and Rhizophora stylosa. Damage assessment showed that 47.28% and 17.90% of the mangroves were severely damaged at Sto. Niño and Sta. Margarita, respectively. Recovery and regenerative capacity were also assessed for both sites. During the 1st sampling 66.53% and 97.82% of the mangroves at Sto. Niño and Sta. Margarita had resprouted leaves. A total of 295 seedlings were counted at Sto. Niño while 140 seedlings were at Sta. Margarita. Although both sites showed a decrease in seedling count during the duration of the study, the data gathered shows that both mangrove stands are capable of recovering.